Evaluation of the effects of an Iraqi phosphate bonded investment and two commercial types on the marginal fitness of porcelain- fused- to- metal copings . (Mustansiria Dental Journal, 2024)
The effect of different phosphate- bonded investments on the marginal fitnessof porcelain- fused—to-metal copings cast by one type of noble alloy and one type ofbase metal alloy was studied. Three types of phosphate—bonded investments (Castorit -Super C, Norvest, and Iraqivest) were used for investing the thirty copings of eachgroup. The marginal fitness of each coping was determined by measuring the verticalmarginal discrepancies between the gingival margin of the coping and the margin ofthe preparation at four reference points on the labial, mesial, palatal and distal aspectsof the die by the aid of light traveling microscope .The statistical analysis of the results showed that there were significantdifferences in marginal fitness among different investments for both Pd- Ag& Ni-Cralloys. The Castorit- Super C and Norvest investments produced comparable resultswith both alloys, while the Iraqivest appeared less compatible with Pd-Ag alloy thanthe other two investments and it had comparable compatibility to Norvest investmentwhen used with Ni- Cr alloy. The Ni- Cr alloy (Heraenium NA) copings revealedsignificantly greater marginal discrepancy than the Pd-Ag alloy (QD) eopingsspecially when using Castorit- Super C and Norvest investments .